New records of bats from Peru - Medina, César E. (2023)
We presented the first record of three species bats for Peru based on specimens collected between 2007 and 2014. These are Eumops glaucinus, captured in the rainforest from the center of Peru, Molossus bondae captured in the Pacifico rainforest, and Promops nasutus, captured in the montane forests from southeastern. The new records increase the mammal diversity of Peru to 579 species.